Incidentalomas associated with abdominal and pelvic CT angiograms for abdominal-based breast free flap reconstruction. Issue 5 (May 2016) - Ho, Olivia A.; Bagher, Shaghayegh; Jaskolka, Jeff; Tan, Marcus; Butler, Kate; O'Neill, Anne C.; Zhong, Toni; Hofer, Stefan O.
Summary: Computed tomography angiography (CTA) is routinely performed prior to breast reconstruction using deep inferior epigastric perforator (DIEP) flaps to provide better surgical planning and improve preoperative decision making. These investigations occasionally result in unexpected findings in otherwise asymptomatic women. Unexpected findings on imaging in a population of women with previous breast cancer or strong breast cancer risk factors can lead to undue stress and anxiety. The aim of this study is to determine the incidence of unexpected findings in preoperative CT angiograms and to correlate these with patient and breast cancer characteristics. A retrospective chart review from May 2008 to December 2012 was performed reviewing all patients who underwent DIEP flap breast reconstruction. Radiology reports of their preoperative CT angiograms, details of unexpected findings, patients' past medical and cancer history, additional radiological investigations, outcomes, and interventions were reviewed. In total, 360 patients met the inclusion criteria for the study. Sixty-four percent of the patients who underwent CTA imaging had incidental findings. Further imaging was suggested in 48% of this group. The most common incidentalomas were hepatic (47%), bone (24%), and renal (20%). "Incidentalomas" were associated with patients' underlying comorbidities ( p  = 0.001) and age ( p  = 0.01). "Radiographically suspicious incidentalomas" were associated with the underlying comorbidities ( p  = 0.001). The radiologists most commonly suggested investigation methods such as ultrasound (41%), another CT (28%), bone scan (21%), and magnetic resonance imaging (MRI; 14%). No incidentalomas were found to be malignant on further recommended investigation in this study and no breast cancer reconstruction was delayed as a result of the discovery of incidentalomas or their subsequent investigations. It is important to counsel patients of the possibility of incidental findings and the resulting sequelae prior to CTA investigations for breast cancer reconstruction and involve them in shared decision making if additional investigations are required.